RANCANGAN RUTE DISTRIBUSI MAKANAN RINGAN PADA UKM PD KURNIA CIAMIS - Hilman, Maman; Gumilar, Gugum; Pratama Ningrat, R. Gamar (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2023)
UKM in Indonesia can be a breakthrough to improve the people's economy in order to achieve an affluent and equitable life. As well as UKM PD Kurnia which is engaged in snacks in the West Java area, precisely in Ciamis district, Cipaku district which is famous for its cassava chips (pikset) products. These UKM have several supply points to meet consumer demand, but this company has not paid much attention to the distribution system that has been implemented so that the current distribution is not carried out effectively and efficiently. Solving problems in this study include how the distribution route of snack products is currently being applied by UKM PD Kurnia and how to determine the optimal route using the Branch and bound method.Based on the results of the study, obtained 2 optimal routes including outlets (A-7-1-6-4-3-2-5-A) and (A-7-1-6-4-3-5-2-A) from the initial mileage of 107.4 km to 83.2 km resulted in a distance savings of 91.8 km. The distribution cost savings from fuel is Rp. 91,289 deducted from the optimal distance fee of Rp. 70,720. the cost savings achieved by the distribution route is Rp. 20,569 .